Towards Tumor Targeting via Invasive Assay Using Magnetospirillum magneticum - Xavierselvan, Marvin; Divecha, Heena R.; Hajra, Mamta; Silwal, Sushila; Macwan, Isaac (Frontiers in Microbiology, 2021)
Magnetospirillum magneticum (AMB-1) are a species of magnetotactic bacteria that are capable of orienting along the earth’s magnetic field lines through their organelles called magnetosomes. Many studies have shown that certain engineered bacteria can infect the tumor cells resulting in a controlled death of a tumor. This work deals with a technique utilizing AMB-1 along a predefined path through magnetotaxis, which can pave a way for selective doping as well as isolation of the tumor cells from a group of healthy cells through a Magnetic Invasive Assay. For such a control, tiny mesh of vertical electrical coils each having a diameter of ~3 mm is fabricated, which establishes the path for the bacteria to move along the magnetic field lines. The molecular dynamics simulations at the interface of the bacterial cell surface proteins (MSP-1 & flagellin) and Chinese Hamster Ovary (CHO) cell surface containing cytoplasmic and extracellular proteins (BSG, B2M, SDC1, AIMP1, and FOS) are shown to establish an association between the invading AMB-1 and the host CHO cells. It is found that the CHO protein structure is compromised which disables the activation of its defense function allowing the bacteria to interact and survive. The experimental demonstration involves the CHO cells interactions with the AMB-1 and isolation of selected CHO cells. It is found that AMB-1 integrated CHO cells successfully moved along the magnetic field lines generated by the coils. Statistical analysis performed for the assay showed that AMB-1 cells were found to be viable after invading CHO cells and number of viable cells post co-incubation over a period of 24 hours showed a slight decrease in both cell population. Overall, 51% of AMB-1 cells and 67% of CHO cells were found viable 24 hours post co-incubation. Scanning electron microscopy along with energy-dispersive X-ray spectroscopy analysis revealed AMB-1/CHO cells morphology, potential interaction between them and the presence of magnetosomes with trace amounts of iron in the AMB-1 invaded CHO cells confirming the successful AMB-1 invasion.